(untitled) (Journal of Medical Device Technology, 2022)
Every workplace has always various potential risk that can affect the health of the workers or can cause work-related illnesses. One of the physical conditions and work environment that is dangerous is noise. The higher intensity of noise and the longer the workers are exposed to noise, the higher the risk of workers experiencing hearing loss. The purpose of this study was to determine the relationship of risk factors with noise due to hearing disorder in furniture workers along Jalan Pahlawan in Medan City, Sumatera Utara Province, Indonesia, 2019.This study was an observational analytic study with a cross sectional research design. This study uses a population of furniture workers along Jalan Pahlawan and using accidental sampling in the sampling method of 30 respondents. Data was carried out by measuring the noise intensity in the work area of ​​furniture production and give questionnaires to 30 respondents who are working. Data analysis techniques used are univariate and bivariate analysis. The results of the study show that there is a relationship between noise intensity and hearing disorder (p=0,001<α=0,05); there is a relationship between the age of the worker and hearing disorder (p=0,000<α=0,05); there is a relationship between period of work with hearing disorder (p=0,025<α=0,05); there is a duration of work relationship with hearing disorder (p=0,010<α=0,05); there is a relationship between the use of ear protector and hearing disorder(p=0.001<α=0,05) in furniture workers along Jalan Pahlawan in Medan City.